Design thinking for tech: solving problems and realizing value in 24 hours - Anderson, George (Pearson, 2024)
Design Thinking is both a process and a set of techniques and exercises useful for thinking through and solving problems faster than otherwise possible. Hour 1 commences Part I called "Design Thinking Basics," where we assemble and align around the Design Thinking Cycle for Progress and a Design Thinking Model for Tech (Hours 1-5). Subsequent Parts of the book include Part II Understanding Broadly (Hours 6-9), Part III, "Thinking Differently" (Hours 10-14), Part IV, "Delivering Value" (Hours 15-18), and Part V, "Iterating for Progress" (Hours 19-24)"--